Effect of Different Surface Treatments on Repair Micro-shear Bond Strength of Silica- and Zirconia-filled Composite Resins - Mohammad Joulaei; Mahmoud Bahari; Anahid Ahmadi; Siavash Savadi Oskoee (Tabriz University of Medical Sciences, 2012)
Background and aims. Effect of surface treatments on repair bond strength of aged composite resins might be different due to their dissimilar fillers. The aim was to evaluate the effect of different surface treatments on repair micro-shear bond strength (µSBS) of silica- (Spectrum TPH) and zirconia-filled (Filtek Z250) composite resins. Materials and methods. Twenty-seven composite resin blocks were made from each type of composite resin: Z250 and Spectrum TPH. After aging, blocks of each type were randomly divided into three groups according to surface treatments: alloy primer, silane, and only surface roughening. Subsequently, each group was further subdivided into 3 subgroups based on the adhesive system used: Single Bond, Clearfil SE Bond, and Margin Bond. Four composite resin columns were added on each block. After thermocycling, µSBStest were done at cross head speed of 0.5 mm/min. Data was analysed using multifactor ANOVA, one-way ANOVA and a post-hoc Bonferroni tests (α = 0.05). Results. Analysis of data showed that the effect of composite resin type was not significant (p > 0.05), but the effects of the type of surface treatment (p = 0.01) and the type of adhesive system (p = 0.01) were significant on repair µSBS. In addition, the cumulative effect of the composite type-surface treatment and the composite type with the type of adhesive system were not statistically significant (p > 0.05). However, the cumulative effects of the adhesive system-surface treatment (p = 0.03) and the composite type-the adhesive system-surface treatments (p = 0.002) were significant. Conclusion. Although repair µSBS values of both silica- and zirconia-filled composite resins were similar, use of different combinations of surface treatments and adhesive systems affected their repair µSBS differently.